Liver laceration as a post-cardiopulmonary resuscitation complication in a person with breast implants: a case report - Min-Jeong Cho (Journal of Trauma and Injury)
Cardiac compression is the most crucial component of successful cardiopulmonary resuscitation (CPR). However, CPR procedure poses a risk of complications, even when CPR providers perform cardiac compressions as recommended. Reports indicate that solid organ injuries, including liver injuries, occur with an incidence of about 0.6% to 3%. In this particular case, a 25-year-old woman was found hanged in her apartment. She was transported to a nearby hospital where CPR was administered for approximately 30 minutes until she was resuscitated. Subsequently, an abdomen-pelvis computed tomography scan revealed a liver injury. The location of the liver injury, between the sternum and spine, suggested it was a compression injury caused by CPR. There was no evidence of extravasation or active bleeding; thus, conservative management was chosen for the liver injury. By hospital day 4, the patient's pupil reflex had completely disappeared. Electroencephalography showed generalized attenuation, indicating severe global brain damage. Liver injury is a relatively rare post-CPR complication, with an incidence of 0.6% according to a retrospective analysis of a cardiac arrest registry. The liver is partially situated between the sternum and spine. The end of the sternum is shaped like an inverted triangle, resembling a sword. Therefore, if the CPR provider's hands are placed too low or excessive pressure is applied, the sternum can injure the left liver. Blood loss from liver injuries could potentially hinder the successful resuscitation of patients. In this case, had there been no blood loss from the liver injury, the patient might have maintained better cerebral perfusion and function.